PENINGKATAN PRESTASI BELAJAR SISWA MELALUI SELF-REGULATED LEARNING - Muhammad Nur Wangid (LPMPP Universitas Negeri Yogyakarta, 2004)
An educational system should be able to develop students' ability to learn. Students who have good learning habits and ability could begiven the J:eSPonsibilit¥ and ability ofregulating their own learning activities. Itmeans that it would be the students themselves who would execute the processes of exploration, inquiry, and learning and also conceptualize their activities. Students' learning activities would not work ifthe teacher's conceptofinstruction still uses the approach ofthe